EXPLORING THE DIVIDE: MODERNITY AND PRIMITIVISM IN ARUN JOSHI’S ‘THE STRANGE CASE OF BILLY BISWAS’ - Tyagi, Indu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper examines the thematic tension between modernity and primitivism in Arun Joshi’s The Strange Case of Billy Biswas, focusing on the protagonist’s quest for self-discovery and spiritual regeneration. The novel criticizes post-independence Indian society’s moral and cultural decay, juxtaposing the superficial materialism of urban elites with the spiritual authenticity of tribal life. Billy Biswas, disillusioned with modern civilization, abandons its artificiality in favor of a primitive existence that restores his sense of purpose and connection with nature. The story vividly depicts his transformation, revealing both the hollowness of modernity and the redemptive power of primal values. Joshi’s juxtaposition of the civilized world with tribal innocence serves as a profound meditation on identity, existential alienation, and the search for authenticity in a mechanized world.